A new synonym of Bulbophyllum ovalifolium (Orchidaceae: Epidendroideae) - Metusala, Destario; Wibowo, Aninda Retno Utami; Mambrasar, Yasper Michael; Hendrian, Hendrian (Phytotaxa, 2020)
Bulbophyllum trinervosum (Orchidaceae) was described in mid 2020 as a new species from West Java, Indonesia. After careful examination and morphological comparisons, it has been concluded that the characters of B. trinervosum fall within the variation of widespread species, B. ovalifolium. Thus, B. trinervosum is proposed here as a synonym of B. ovalifolium. Detailed comparisons, including a series of photos of B. ovalifolium are provided.